Competências do enfermeiro em ventilação invasiva: um estudo metodológico - Santos, Luiz Fernando Souza (2023)
Introduction: The management of patients using invasive mechanical ventilation becomes a daily challenge for health professionals working in the Intensive Care Unit, requiring the presence of a qualified interdisciplinary team. The nurse who manages patient care in invasive mechanical ventilation needs to have well-developed skills, knowledge, and competencies. Objective: To develop an instrument to assess nurses' skills in caring for patients on invasive mechanical ventilation. Method: Methodological study, using psychometric procedures for constructing and validating instruments as a reference, based on a theoretical approach, which consisted of developing a scope review. The scope review was developed based on the JBI guidelines for scoping reviews and PRISMA – Preferred Reporting Items for Systematic Reviews and MetaAnalyses, an extension for scope reviews, and was registered on the Open Science Framework (OSF) platform identified by DOI 10.17605 /OSF.IO/6CSFM. The instrument was developed using psychometric procedures for constructing and validating instruments as a reference. Results: In this study 33 articles were selected to compose the scoping review, whose predominant domains were knowledge about mechanical ventilation, ability to perform techniques related to nursing care, interaction with an interdisciplinary team and competence in the execution of nursing care. The results of the scope review served as a subsidy for the development of an instrument to assess nurses' competences for the care of patients on invasive mechanical ventilation, having as categories the assessment of knowledge, skills, and attitudes. Conclusion: The triad of knowledge, skill and attitude encompasses the role of nurses in assisting patients undergoing invasive mechanical ventilation, this is due to the versatility of nursing care. With the construction of the instrument and its validation, nurses will have the opportunity to evaluate their knowledge, skills, and attitudes in relation to the care provided, as well as teachers or coordinators of hospital institutions. Furthermore, the instrument's items can serve as a basis for the development of such competencies, serving as guidance on essential knowledge, skills and expected attitudes.